70 Anniversary: Vakarchuk I.O. - ojsadmin, ojsadmin (Physics and Chemistry of Solid State, 2019)
Honored Scientist of Ukraine, Doctor of Physical and Mathematical Sciences, Professor, Minister of Education and Science of Ukraine (2007-2010), Rector of Ivan Franko Lviv State University (1990-2007 and 2010-2013), Hero of Ukraine (2007) , politician and public person.